Code Switching and Code Mixing Analysis in the Activities of the Avicenna Language Rayon Writing Class: A Sociolinguistic Study - Oktavia Winda Lestari (Bulletin of Social Studies and Community Development, 2024)
Abstract: This research started from the results of observations carried out in the Avicenna Language District. Based on observations, it is known that in the process of writing class activities tend to use code switching and code mixing. This study aims to describe the types of code switching, code mixing, the form of code switching, and the factors that cause code switching and code mixing in Avicenna's writing class activities. The method in data analysis is a qualitative description method. Data collection techniques through participant observation using recording and note-taking techniques. Meanwhile, data analysis uses inductive data analysis to find research results by categorizing specific things that have been found to be directed to general categories. The results of the analysis obtained in this study.     Keywords: code switch, code mix, factor, avicenna, an sociolinguistic study.